DCP as a biomarker for TACE efficacy in hepatocellular carcinoma - Xie, Hui; Li, Youwei; Yang, Jie; Tan, Yuwei; Xu, Jin; Yang, Xiao (Frontiers in Oncology, 2025)
IntroductionPrimary hepatocellular carcinoma (PHC) requires advanced diagnostic and therapeutic strategies. While transcatheter arterial chemoembolization (TACE) is a cornerstone treatment, efficacy assessment remains challenging.MethodsWe retrospectively analyzed 90 PHC patients treated with TACE. Serum DCP levels were measured pre-treatment and at 1, 4, and 8 weeks post-treatment. Treatment response was evaluated using mRECIST criteria.ResultsLow DCP patients (≤40 mAU/mL) showed significantly higher response rates (53.3%) compared to high DCP (>300 mAU/mL, 30.0%, p<0.05). The hazard ratio for treatment failure was 1.62 (95% CI: 1.09–2.23, p<0.01) per unit increase in log-transformed DCP. Median overall survival was 24.5 months for low DCP versus 12.6 months for high DCP patients (log-rank p<0.001).DiscussionDCP serves as a robust biomarker for predicting TACE efficacy, enabling personalized treatment strategies in PHC management.